Ecophysiology of crytocoryne zaidiana ipor & tawan (araceace) - Hafizan, binti Selamat. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Study on response of Cryptoeoryne zaidiana Jpor & Tawan to shading and water depths was conducted at Universiti Malaysia Sarawak. Plants were exposed to different light regimes (tree canopy shading, 75% light intensity and 50% light intensity) and water depth regimes (0 cm, IO cm, and 30 cm) to detennine its growth rate, biomass allocation and photosynthesis rate. Pulse amplitude modulated fluorometer (Diving-Pam, Walz Gmbh, Gennany) equipment was used to measure the photosynthetic activity of photosystem II (PS II). Possibility of using rhizome cutting in plant propagation was carried out using I node, 3 nodes and 5 nodes cuttings.